(untitled) (World Economics and Finance Bulletin, 2022)
The study aims to demonstrate the appropriateness of measurement and accounting disclosure of biological assets in agricultural establishments within the framework of International Accounting Standard 41, which clearly requires the use of fair value measures when measuring animal or plant biological assets and to indicate the extent to which these treatments are compatible with practical application practices, in addition to indicating the importance of applying International Standard 41 determines the problems of measurement and accounting disclosure in the activity of animal and plant production and sets strict controls in this regard, which leads to the lack of multiple alternatives to measurement and accounting disclosure and obtaining reliable and comparable accounting information, and thus this information affects the decision of investors and all parties benefiting from those the information . The problem of the study is represented by asking the question: Is International Accounting Standard 41 suitable for measurement and accounting disclosure of biological assets in agricultural facilities.